Riding the rails of removal: The impact of railways on border controls and expulsion practices. Issue 2 (August 2019) - Feys, Torsten
Nineteenth-century Belgian authorities liked to consider themselves as liberal towards migrants, but the 340, 000 expulsions carried out between 1835 and 1913 paint a different picture. This article assesses how the development of Belgian railway networks influenced controls of entry and expulsion practices through seven borderland hubs with international rail connections. It first details how control stations followed changes in transport infrastructure and that some form of border control on human mobility was upheld throughout the nineteenth century. Second, it explains how railways drastically changed expulsions allowing the Sûreté Publique (i.e. the Belgian Foreigners Police) to establish a well-oiled deportation apparatus which became a central pillar of migration policies. Using Walters' concept of "viapolitics", it details how transport systems and infrastructure shaped the state's ability to govern migrants.